2016
DOI: 10.1080/14763141.2016.1194453
|View full text |Cite
|
Sign up to set email alerts
|

Specific tackling situations affect the biomechanical demands experienced by rugby union players

Abstract: Tackling in Rugby Union is an open skill which can involve high-speed collisions and is the match event associated with the greatest proportion of injuries. This study aimed to analyse the biomechanics of rugby tackling under three conditions: from a stationary position, with dominant and non-dominant shoulder, and moving forward, with dominant shoulder. A specially devised contact simulator, a 50-kg punch bag instrumented with pressure sensors, was translated towards the tackler (n = 15) to evaluate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 28 publications
(53 reference statements)
2
39
1
Order By: Relevance
“…Although results from lab-based studies may have limited applicability to match situations due to its controlled nature, studying the tackle in the lab allows for experiential and explorative study designs. Experiential and explorative study designs may offer deeper insights into the demands and movement patterns of the tackle (eg, tackle biomechanics), 103 as well as test the effects of different conditions (eg, physical fatigue) and interventions (video feedback) 143 on tackle technique. Not all research on the tackle needs to have a direct application, and experiential and explorative work is important to inspire innovative tackle injury prevention and performance strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although results from lab-based studies may have limited applicability to match situations due to its controlled nature, studying the tackle in the lab allows for experiential and explorative study designs. Experiential and explorative study designs may offer deeper insights into the demands and movement patterns of the tackle (eg, tackle biomechanics), 103 as well as test the effects of different conditions (eg, physical fatigue) and interventions (video feedback) 143 on tackle technique. Not all research on the tackle needs to have a direct application, and experiential and explorative work is important to inspire innovative tackle injury prevention and performance strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Site-specific response of bone to a stressful mechanical environment can be observed in male tennis and baseball players, whose playing arms demonstrate significantly greater BMD and BMC of up to 24% and 45% respectively compared with their non-playing arms (Calbet et al, 1998;Ducher et al, 2009Ducher et al, , 2006Ducher et al, , 2005Haapasalo et al, 2000;Ireland et al, 2013;Sanchis-Moysi et al, 2010;Warden et al, 2009) This response was suggested to be due to the osteogenic effect of the muscles surrounding the shoulder, elbow and wrist acting upon the bones of the arm, producing a large mechanical strain, stimulating a response (Burr et al, 1997). The response of the lumbar spine to stressful mechanical environment can be observed in male rugby players, who demonstrate significantly elevated BMD and BMC at the lumbar spine than a control population (Elloumi et al, 2009;Hind et al, 2014) in response to the high bilateral forces sustained by the trunk during collisions, tackling and while scrummaging (Milburn, 1993;Seminati et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…IRD showed no statistically relevant differences in both groups in this study. An increased IRD distance is related to pelvic floor disorders and urinary incontinence [42], which has a higher prevalence in athletic women compared to sedentary populations [56]. IRD in women is principally altered during postpartum [41].…”
Section: Discussionmentioning
confidence: 99%